Environmental Capacity And Sustainability Of European Regional Airports: A Case Study - Gualandi, Nicola; Mantecchini, Luca; Serrau, Davide (Zenodo, 2008)
Airport capacity has always been perceived in the traditional sense as the number of aircraft operations during a specified time corresponding to a tolerable level of average delay and it mostly depends on the airside characteristics, on the fleet mix variability and on the ATM. The adoption of the Directive 2002/30/EC in the EU countries drives the stakeholders to conceive airport capacity in a different way though. Airport capacity in this sense is fundamentally driven by environmental criteria, and since acoustical externalities represent the most important factors, those are the ones that could pose a serious threat to the growth of airports and to aviation market itself in the short-medium term. The importance of the regional airports in the deregulated market grew fast during the last decade since they represent spokes for network carriers and a preferential destination for low-fares carriers. Not only regional airports have witnessed a fast and unexpected growth in traffic but also a fast growth in the complaints for the nuisance by the people living near those airports. In this paper the results of a study conducted in cooperation with the airport of Bologna G. Marconi are presented in order to investigate airport acoustical capacity as a defacto constraint of airport growth. : {"references": ["B. Graham and C. Guyer, \"Environmental sustainability, airport capacity\nand European air transport liberalization: irreconcilable goals,\" Journal\nof Transport Geography, vol. 7, pp. 165-180, 1999.", "R. Horonjeff, F.X. McKelvey, \"Planning and Design of Airports,\" Ed.\nMcGraw-Hill: New York, 1993.", "K. Hume, M. Gregg, C. Thomas and D. Terranova, \"Complaints Caused\nby Aircraft Operations: an Assessment of Annoyance by Noise Level an\nTime of the Day,\" Journal of Air Transport Management, vol. 9, pp.\n153-160, 2003.", "M. Ignaccolo, \"Environmental capacity: noise pollution at Catania-\nFontanarossa international airport,\" Journal of Air Transport\nManagement, vol. 6, pp. 191-199, 2000.", "The Manchester Metropolitan University, \"The Concept of Airport\nEnvironmental Capacity,\" Department of Environmental and\nGeographical Science, October 2002.", "H. M. E. Miedema and C. G. M. Oudshoorn, \"Annoyance from\ntransportation noise: relationship with exposure metrics DNL and DENL\nand confidence intervals\", Environmental Health Prospectives, vol. 109,\npp. 409-416, 2001.", "R. de Neufville and A. R. Odoni, \"Airport Systems: Planning, Design\nand Management,\" Ed. McGraw-Hill: New York, 2003.", "R. L. Paullin \"Capacity and Noise Relationships for Major Hub\nAirports,\" proceedings of the IEEE, vol. 58, pp. 307-313, March 1970.", "R. Rylander and M. Bj\u00f6rkman, \"Annoyance by aircraft noise around\nsmall airports\", Journal of Sound and Vibration, 205 (4), PP.533-537,\n1997.\n[10] M. J. T. Smith, \"Aircraft Noise\", Ed. Cambridge: Cambridge\nUniversity Press, 1989.\n[11] P. Upham, C. Thomas, D. Gillingwater and D. Raper, \"Environmental\nCapacity and Airport Operations: Current issues and Future Prospects,\"\nJournal of Air Transport Management, vol. 9, pp 145-151, 2003.\n[12] P. Upham, D. Raper, C. Thomas, M. McLellan, M. Lever, A. Lieuwen,\n\"Environmental Capacity and European Air Transport: Stakeholder\nOpinion and Implications for modeling,\" Journal of Air Transport\nManagement, vol. 10, pp 199-205, 2004."]}